Using the Interval Type-2 Fuzzy Inference Systems to Compare the Impact of Speed and Space Perception on the Occurrence of Road Traffic Accidents - Čubranić-Dobrodolac, Marjana; Švadlenka, Libor; Cicevic, Svetlana; Trifunovic, Aleksandar; Dobrodolac, Momčilo (MDPI, 2020)
A constantly increasing number of deaths on roads forces analysts to search for models that predict the driver's propensity for road traffic accidents (RTAs). This paper aims to examine a relationship between the speed and space assessment capabilities of drivers in terms of their association with the occurrence of RTAs. The method used for this purpose is based on the implementation of the interval Type-2 Fuzzy Inference System (T2FIS). The inputs to the first T2FIS relate to the speed assessment capabilities of drivers. These capabilities were measured in the experiment with 178 young drivers, with test speeds of 30, 50, and 70 km/h. The participants assessed the aforementioned speed values from four different observation positions in the driving simulator. On the other hand, the inputs of the second T2FIS are space assessment capabilities. The same group of drivers took two types of space assessment tests-2D and 3D. The third considered T2FIS sublimates of all previously mentioned inputs in one model. The output in all three T2FIS structures is the number of RTAs experienced by a driver. By testing three proposed T2FISs on the empirical data, the result of the research indicates that the space assessment characteristics better explain participation in RTAs compared to the speed assessment capabilities. The results obtained are further confirmed by implementing a multiple regression analysis.
Využití fuzzy inferenčních systémů typu 2 k porovnání dopadu rychlosti a vnímání prostoru na výskyt dopravních nehod
Keywords: type-2 fuzzy inference systems; traffic simulator; traffic accidents; road safety; space perception; speed perception; fuzzy; inferenční systém; porovnání; dopad; rychlost; vnímání; prostor; výskyt; dopravní nehody